Learning from the Perspectives of Albert Bandura and Abdullah Nashih Ulwan: Implications Towards the 21st Century Education - Abdullah, Norillah; Syed Hassan, Sharifah Sariah; Abdelmagid, Mohamed; Mat Ali, Siti Nazilah (IAIN Samarinda, 2020)
A vast existing literature in educational research has been explored on Social Cognitive Theory (SCT) with the focus on addressing self-efficacy, self-regulation and social interactions in learning. This theory is used as a framework to predict behaviours and interventions. However, researchers have managed to comprehend and adopt the theory comprehensively with regards to all the factors involved specifically in the domain of pedagogical potentials in education and metaphysics. Thus, this paper has two-fold purposes. Firstly, this paper seeks to revisit the SCT from Islamic perspectives. Secondly, it attempts to propose a new pedagogical framework adapted from both theories for enhancing classroom teaching and learning. For this, the theoretical approach of Abdullah Nashih Ulwan has been compared and contrasted with an analytical approach by framing the references of the theory and the domain in education and well-being. Based on the analytic summary, this research has adopted comparative holistic visual representation by analyzing the SCT and Islamic perspectives. In consequence, a proposed learning model is given for a comprehensive view from both perspectives. The findings will advocate teachers and researchers when dealing with holistic human behaviour and personality development.